2018
DOI: 10.3390/molecules23081938
|View full text |Cite
|
Sign up to set email alerts
|

Styryl Quinazolinones as Potential Inducers of Myeloid Differentiation via Upregulation of C/EBPα

Abstract: The CCAAT enhancer-binding protein α (C/EBPα) plays an important role in myeloid cell differentiation and in the enhancement of C/EBPα expression/activity, which can lead to granulocytic differentiation in acute myeloid leukemia (AML) cells. We found that styryl quinazolinones induce upregulation of C/EBPα expression, and thereby induce myeloid differentiation in human myeloid leukemia cell lines. We screened a series of active styryl quinazolinones and evaluated the structure–activity relationship (SAR) of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…S2H ). SPI-1 and C/EBPα were two known transcription factors for up-regulating the expression of CD11b and CD14, and promoting myeloid cell differentiation [ 38 40 ]. We found that overexpression of GPR132 elevated the mRNA levels of SPI1 and CEBPA (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S2H ). SPI-1 and C/EBPα were two known transcription factors for up-regulating the expression of CD11b and CD14, and promoting myeloid cell differentiation [ 38 40 ]. We found that overexpression of GPR132 elevated the mRNA levels of SPI1 and CEBPA (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of reduced CEBPa, increasing the level/activity of this pro-differentiative TF could be a valuable option in promoting granulocytic differentiation. High-throughput screening identified small molecules selectively activating CEBPa [334] and more innovative strategies exploring short-activating RNAs (saRNAs [335]) are under development [336]. Other studies, beyond the main scope of this review, aim to restore CEBPa function by blocking the CEBPa upstream suppressor RAC1 [337] or by targeting the downstream CEBPa p30 tumor-promoting targets [338].…”
Section: Transcription Factors' Targetingmentioning
confidence: 99%
“…The synthesis of the title compound (3) was performed according to synthesis method of styryl quinazolinones derivatives reported earlier [12,13]. A mixture of 3-(4-methoxyphenyl)-3, 3a,4,5,6,7-hexahydro-2H-indazole (115 mg, 0.5 mmol) and 4-methoxy-benzaldehyde (68 mg, 0.5 mmol) was dissolved in glacial acetic acid (10 mL) and refluxed at 120 • C for 3 h until completion (TLC monitoring).…”
Section: Synthesis Of (7e)-3-(4-methoxyphenyl)-7-[(4-methoxyphenyl)mementioning
confidence: 99%